Screening of wild species and transcriptome profiling to identify differentially regulated genes in response to late blight resistance in potato - Bhatia, Nisha; Tiwari, Jagesh Kumar; Kumari, Chandresh; Zinta, Rasna; Sharma, Sanjeev; Thakur, Ajay Kumar; Buckseth, Tanuja; Dalamu, Dalamu; Singh, Rajesh Kumar; Kumar, Vinod (Frontiers in Plant Science, 2023)
Late blight (Phytophthora infestans) is a serious disease of potato. The aim of this study was to screen wild potato species and identify differentially expressed genes (DEGs) associated with late blight resistance. Wild potato species such as PIN45 (Solanum pinnatisectum), CPH62 (S. cardiophyllum), JAM07 (S. jamesii), MCD24 (S. microdontum), PLD47 (S. polyadenium) and cv. Kufri Bahar (control) were tested by artificial inoculation of P. infestans under controlled conditions. Transcriptome of the leaf tissues (96 h post-inoculation) were sequenced using the Illumina platform. Statistically significant (p < 0.05) DEGs were analyzed in wild species by comparison with the control, and up-regulated (> 2 log2 fold change, FC) and down-regulated (< -2 log2 FC) genes were identified. DEGs were functionally characterized with GO (Gene Ontology) terms and KEGG (Kyoto Encyclopedia of Genes and Genomes) pathways. Selected genes were validated by real-time PCR analysis to confirm RNA-seq results. We identified some up-regulated genes associated with late blight resistance in wild species such as cytochrome P450, proline-rich protein, MYB transcription factor MYB139, ankyrin repeat-containing protein, LRR receptor-like serine/threonine-protein kinase in PIN45; glucosyltransferase, fructose-bisphosphate aldolase, phytophthora-inhibited protease 1 in CPH62; steroid binding protein, cysteine proteinase 3 in JAM07; glycine-rich cell wall structural protein 1 and RING finger protein in MCD24; and cysteine proteinase 3 and major latex protein in PLD47. On the other hand, down-regulated genes in these species were snakin-2 and WRKY transcription factor 3 in PIN45; lichenase and phenylalanine ammonia-lyase 1 in CPH62; metallothionein and LRR receptor-like serine/threonine-protein kinase in JAM07; UDP-glucoronosyl/UDP-glucosyl transferase family protein and steroid binding protein in MCD24; and cytoplasmic small heat shock protein class I and phosphatase PLD47. Our study identified highly resistant wild potato species and underlying genes such as disease resistance, stress response, phytohormones and transcription factors (e.g. MYB, WRKY, AP2/ERF, and AN1) associated with late blight resistance in wild potato species.